2016
DOI: 10.1007/s00417-016-3290-5
|View full text |Cite
|
Sign up to set email alerts
|

Epo inhibits the fibrosis and migration of Müller glial cells induced by TGF-β and high glucose

Abstract: High glucose together with TGF-β promote MGCs to exhibit a fibroblast-like phenotype and develop a greater migratory ability. These changes can be inhibited by Epo, which therefore may contribute to the controlling of epiretinal membrane formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…We therefore examined whether hyperglycemia was sufficient for increasing mesenchymal marker levels in retinal Müller cells. As was the case in a previous study [29], we found that high glucose conditions increased α-SMA, fibronectin, and connective tissue growth factor (CTGF) levels in Müller cells. Furthermore, we found that high glucose conditions also increased N-cadherin, β-catenin, Vimentin, and Snail levels (Figure 4).…”
Section: Discussionsupporting
confidence: 83%
“…We therefore examined whether hyperglycemia was sufficient for increasing mesenchymal marker levels in retinal Müller cells. As was the case in a previous study [29], we found that high glucose conditions increased α-SMA, fibronectin, and connective tissue growth factor (CTGF) levels in Müller cells. Furthermore, we found that high glucose conditions also increased N-cadherin, β-catenin, Vimentin, and Snail levels (Figure 4).…”
Section: Discussionsupporting
confidence: 83%
“…Li et al [34] also found that oxidative stress is the main reason for the decrease of EPO expression in aging of rats. In addition to the inhibition of oxidative stress and inflammation, EPO can also inhibit fibrosis of renal tubular epithelial cells by inhibiting EMT, where EPO downregulates the expression of TGF-β, α-SMA, fibronectin, and connective tissue growth factor [35]. However, many original research studies showed that soluble EPOR levels may contribute to erythropoietin resistance in ESRD and that soluble EPOR production may be mediated by proinflammatory cytokines [36].…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor-b induces the differentiation of these cells into a fibroblast-like phenotype and promotes their migration. 7,8 Characteristic cytokine profiles for the differentiation of fibroblasts and retinal glia are unknown, but we assume activated fibroblasts as a source, but not so evidently Müller glia cells, in the chronic phase of ERM formation. The cytokine profiles in our study are commensurate with an activation of fibrotic and inflammatory processes, which are associated with elevated levels of IL-6, IL-4, IL-1b, TNF-a, IL-10, IL-2, and INF-c (among others).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,5 Müller glial cells are known to activate fibroblasts and to promote fibrotic changes within the eye, such as proliferative vitreoretinopathy (PVR) 3,6 and the formation of epiretinal membranes (ERMs). 7,8 Epiretinal membranes are characterized by the growth of fibrocellular tissue along the inner limiting membrane (ILM), which can lead to metamorphopsia and visual loss. The most frequently encountered, so-called idiopathic ERMs, are not linked to any other ocular disease process and their pathogenesis remains unidentified.…”
mentioning
confidence: 99%